Wound healing: insights into autoimmunity, ageing, and cancer ecosystems through inflammation and IL-6 modulation - Lacina, Lukáš; Kolář, Michal; Pfeiferová, Lucie; Gál, Peter; Smetana, Karel (Frontiers in Immunology, 2024)
Wound healing represents a complex and evolutionarily conserved process across vertebrates, encompassing a series of life-rescuing events. The healing process runs in three main phases: inflammation, proliferation, and maturation/remodelling. While acute inflammation is indispensable for cleansing the wound, removing infection, and eliminating dead tissue characterised by the prevalence of neutrophils, the proliferation phase is characterised by transition into the inflammatory cell profile, shifting towards the prevalence of macrophages. The proliferation phase involves development of granulation tissue, comprising fibroblasts, activated myofibroblasts, and inflammatory and endothelial cells. Communication among these cellular components occurs through intercellular contacts, extracellular matrix secretion, as well as paracrine production of bioactive factors and proteolytic enzymes. The proliferation phase of healing is intricately regulated by inflammation, particularly interleukin-6. Prolonged inflammation results in dysregulations during the granulation tissue formation and may lead to the development of chronic wounds or hypertrophic/keloid scars. Notably, pathological processes such as autoimmune chronic inflammation, organ fibrosis, the tumour microenvironment, and impaired repair following viral infections notably share morphological and functional similarities with granulation tissue. Consequently, wound healing emerges as a prototype for understanding these diverse pathological processes. The prospect of gaining a comprehensive understanding of wound healing holds the potential to furnish fundamental insights into modulation of the intricate dialogue between cancer cells and non-cancer cells within the cancer ecosystem. This knowledge may pave the way for innovative approaches to cancer diagnostics, disease monitoring, and anticancer therapy.